The main areas and opportunities for specialised French teaching in Kazakhstan - Канаева, Акмарал; Умекова, Назира (Pedagogy and Psychology, 2022)
In this article we consider the features and advantages of teaching a professionally oriented foreign language to non-linguistic students in universities of Kazakhstan, also we consider the methods used in the learning process. Nowadays, professionally-oriented foreign language teaching is recognised as one of the priorities of the higher education system in the Republic of Kazakhstan. Vocationally-oriented teaching helps to develop the ability to communicate using four speech skills (listening, reading, speaking and writing) depending on the situation. In addition, in this article, we will focus on the main factors that create difficulties in teaching professionally oriented French in Kazakhstani universities. Considering the components of communicative competence formed in the process of teaching this discipline, we determine the importance of language-professional competence and give guidelines aimed at its development. Also, based on the works of methodologists, we define the concept of "communicative competence".